Evolution of butterfly technique when resisted swimming with parachute using different resistances - Llop, F.; Tella, V.; Colado, J. C.; Diaz, G.; Navarro, F. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of the study was to measure the effect on the stroke variables in speed (S), stroke rate (SR), stroke length (SL), and stroke index (SI) during swimming. Six tests were carried out. These tests consisted in swimming butterfly style 25 metres at maximum intensity using normal swimming (NS) and resisted swimming with parachute (RSWP) with a front span of 30cm and a back diameter of 30, 22.5, 15, 7.5 and 0cm. The study was carried out with 18 swimmers between 19 and 22 years of age. An intra-group design of repeated measures was used. The results obtained showed how the SF does not significantly vary with different diameter, but there are significant differences between NS and 0cm, 15cm and 30cm. Significant differences (p<0.000), are produced in SL, S, SI between NS and all other diameter. This Information will allow trainers to improve the mechanics of swimming butterfly style when performing RSWR